Solving the First Order Differential Equations using Newton's Interpolation and Lagrange Polynomial (European Journal of Pure and Applied Mathematics, 2023)
In this paper, we use both Newton’s interpolation and Lagrange polynomial to create cubic polynomials for solving the initial value problems. By this new method, it is simple to solve linear and nonlinear first order ordinary differential equations and to yield and implement actual precise results. Some numerical examples are provided to test the performance and illustrate the efficiency of the method.
Keywords: Numerical analysis; Initial Value Problem; Newton’s Interpolation Formula; Lagrange